Analisis Dasar Pertimbangan Hakim Dalam Menjatuhkan Pidana Dibawah Minimum Khusus Terhadap Tindak Pidana Tanpa Hak Menguasai Narkotika Golongan I - Benny David Silaen; Heni Siswanto; Budi Rizki Husin; Erna Dewi; Mamanda Syahputra Ginting (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The criminal case committed by the defendant in Decision Number 341/Pid.Sus/2024/PN Gns was proven to involve the abuse of methamphetamine for personal use. The issue examined by the author is the judges' consideration in imposing a sentence below the minimum specifically for the defendant and the purpose of sentencing for the defendant. This research uses a normative juridical approach supported by interviews. The research findings show that from a juridical perspective, the judges made a breakthrough based on Supreme Court Circular Letter (SEMA) No. 3 of 2015 by imposing a 1-year prison sentence, which falls below the 4-year minimum threshold stipulated in Article 112 Paragraph (1) of Law Number 35 of 2009. Philosophical and sociological considerations underpinned this decision, as the judges sought substantive justice by examining the defendant's background as a woman, a non-recidivist, and the sole breadwinner for her child suffering from polio. Furthermore, this study identifies a procedural flaw resulting from the absence of both a urine test and a recommendation from the Integrated Assessment Team (TAT). Consequently, the judges did not mandate medical or social rehabilitation measures, shifting the sentencing paradigm entirely toward the Absolute Theory which prioritizes physical retribution. This study recommends that future judges adopt a more active and progressive approach in exercising their procedural authority in line with the spirit of modern sentencing embodied in Law No.1 of 2023.